Avaliação da atividade de três compostos do óleo de melaleuca sobre o Trypanosoma evansi - Baldissera, Matheus Dellaméa (2016)
This study aimed the evaluation of the trypanocidal activity of terpinen-4-ol, γ-terpinene and α-terpinene against Trypanosoma evansi in vivo and in vitro. The in vitro assay was performed in culture medium of T. evansi, using three different concentrations of each compound (0.5, 1.0 and 2.0%), individually and in synergism. Motile (live) trypomastigotes were counted using a Neubauer chamber after 1, 3, 6 and 9 hours of incubation. Death of parasites occurred in a concentration-dependent manner, except for α-terpinene that was able to eliminate all parasites after 1 hour of incubation at all concentrations tested. Seventy mice were equally assigned into 10 groups (A to J) for the in vivo tests. Group A served as a negative control (healthy animals); groups B - J were infected with 0.1 mL of blood containing 105 T. evansi trypomastigotes. Group B served as a positive control; groups C, D and E received oral doses of 1.0 mL kg-1 of terpinen-4-ol, γ-terpinene and α-terpinene, respectively. Associations of the three compounds were orally administered to groups F I: terpinen-4-ol + γ-terpinene to group F, terpinen-4-ol + α-terpinene to group G, α-terpinene + γ-terpinene at 1.0 mL kg-1 (0.5 mL kg-1 for each compound) to group H, terpinen-4-ol + γ-terpinene + α-terpinene at 1.0 mL kg-1 (0.335 mL kg-1 of each compound) to group I. A therapeutic dose of diminazene aceturate (single dose of 3.5 mg kg-1, intraperitoneally) was administered to Group J aiming test validation. Animals in group E (treated with α-terpinene) showed an increase of longevity when compared to animals in group B. However, no curative effectiveness was observed, since all animals in this group died during the observation period. In order to evaluate the association between α-terpinene and diminazene aceturate, twenty-eight mice were assigned into 4 groups (A, B, C and D, n = 7). Group A included animals uninfected (negative control); group B was composed by infected animals (positive control); group C consisted of infected animals treated with diminazene aceturate (single dose of 3.5 mg kg-1, im); and group D consisted of infected animals treated with an association of diminazene aceturate (single dose of 3.5 mg kg-1, im) and α-terpinene (1.0 ml kg-1, orally administered for 10 days). It was observed, as a result of this experiment, an increase in the curative effectiveness (57.14%) in group D when compared to group C, which showed only 14.28% of curative effectiveness. Based on these results, α-terpinene was the compound present in M. alternifolia essential oil that showed trypanocidal activity.